2017
DOI: 10.2196/jmir.7087
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Health Care Social Media Use From Different Stakeholder Perspectives: A Content Analysis of an Online Health Community

Abstract: BackgroundHealth care social media used for health information exchange and emotional communication involves different types of users, including patients, caregivers, and health professionals. However, it is difficult to identify different stakeholders because user identification data are lacking due to privacy protection and proprietary interests. Therefore, identifying the concerns of different stakeholders and how they use health care social media when confronted with huge amounts of health-related messages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 40 publications
3
70
0
2
Order By: Relevance
“…For example, the use of social media in the fields of child-feeding behaviors, food skills self-efficacy and acquisition, and the dissemination and implementation of social media-based nutrition interventions are yet to be investigated. As opposed to other fields in health care, such as medicine [ 103 - 105 ] and online health communities [ 106 ] for which content analyses of social media tools have been previously published, we only identified 2 content analysis studies of social media written by RDs and both focused on food blogs. Further comparative content analysis of social media written by RDs compared with layperson would help deepen our understanding of the quality and extent of nutrition information disseminated through social media.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of social media in the fields of child-feeding behaviors, food skills self-efficacy and acquisition, and the dissemination and implementation of social media-based nutrition interventions are yet to be investigated. As opposed to other fields in health care, such as medicine [ 103 - 105 ] and online health communities [ 106 ] for which content analyses of social media tools have been previously published, we only identified 2 content analysis studies of social media written by RDs and both focused on food blogs. Further comparative content analysis of social media written by RDs compared with layperson would help deepen our understanding of the quality and extent of nutrition information disseminated through social media.…”
Section: Discussionmentioning
confidence: 99%
“…Doing-Harris et al designed a topic classifier and identified common topics on patient comments to understand patient satisfaction toward health services [ 37 ]. Lu et al determined the hot topics and measured sentiment expression of different stakeholders to understand their different perspectives [ 38 ]. Guillory et al used Twitter data to analyze e-cigarette discussions based on discussion theme and sentiment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this popularity, visual communication of cancer on social media remains underinvestigated. Extant research on social media content related to cancer has focused on text-based content, such as that on Twitter [ 5 , 6 ]. Only a limited number of studies have investigated visual cancer communication on social media [ 7 , 8 ], and few have examined the effects of visual cancer communication on social media.…”
Section: Introductionmentioning
confidence: 99%